2006
DOI: 10.1111/j.1525-139x.2006.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

CRITICAL CARE ISSUES FOR THE NEPHROLOGIST: Low‐dose Dopamine in the Intensive Care Unit

Abstract: For much of the last four decades, low-dose dopamine has been considered the drug of choice to treat and prevent renal failure in the intensive care unit (ICU). The multifactorial etiology of renal failure in the ICU and the presence of coexisting multisystem organ dysfunction make the design and execution of clinical trials to study this problem difficult. However, in the last decade, several meta-analyses and one large randomized trial have all shown a lack of benefit of low-dose dopamine in improving renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…When restricted to neonates whose starting UOP was <1.5 mL/kg/hr, we found twice the increase in UOP compared to the entire cohort that received low-dose dopamine. Our findings are consistent with previous reports in which low-dose dopamine was associated with increased UOP, but not associated with improvements in serum creatinine (8, 10, 11). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…When restricted to neonates whose starting UOP was <1.5 mL/kg/hr, we found twice the increase in UOP compared to the entire cohort that received low-dose dopamine. Our findings are consistent with previous reports in which low-dose dopamine was associated with increased UOP, but not associated with improvements in serum creatinine (8, 10, 11). …”
Section: Discussionsupporting
confidence: 93%
“…Theoretically, low-dose dopamine should result in increased UOP (13). Although there has been significant debate about its use for this purpose in pediatric and adult ICU populations (including suggestion that its use be abandoned) (6, 10, 14), there has been little study dedicated to the VLBW and ELBW neonate. There have been studies that show older animals have increased renal blood flow and naturesis secondary to dopamine compared to younger animals, suggesting a maturation of the dopamine receptor (15).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have even found that low-dose dopamine may actually worsen renal perfusion [72]. Finally both high-quality mRCTs and metaanalyses failed to demonstrate any effect of lowdose dopamine on incidence or clinical course of AKI or mortality [73,74].…”
Section: Dopaminementioning
confidence: 99%
“…However, 'low-dose' or 'renal-dose' dopamine has not been shown to be effective in preventing AKI (Karthik and Lisbon 2006), after investigations in many different clinical scenarios and in some studies in which urine output and/or creatinine clearance improved. Dopamine (0.5-2 mg kg À1 min À1 ) has almost exclusively dopaminergic (as opposed to beta-and alpha-adrenergic) effects that include renal arterial dilation and increased renal blood flow.…”
Section: Preventionmentioning
confidence: 99%
“…In a trial of thyroxine, greater mortality was seen in the treatment arm (43 vs 13%) (Acker et al 2000). Diuretics and dopamine have also been ineffective in improving outcomes in AKI (Karthik and Lisbon 2006). Diuretics and dopamine have also been ineffective in improving outcomes in AKI (Karthik and Lisbon 2006).…”
Section: Specific Treatmentmentioning
confidence: 99%